Multi-site intervention to improve emergency department care for patients who live with opioid use disorder: A quantitative evaluation. Issue 6 (November 2020) - McLane, Patrick; Scott, Ken; Suleman, Zainab; Yee, Karen; Holroyd, Brian R.; Dong, Kathryn; Ghosh, S. Monty; Fanaeian, Josh; Deol, Jan; Biggs, Catherine; Lang, Eddy; et al.
ABSTRACT: Background: Opioid use disorder is a major public health crisis, and evidence suggests ways of better serving patients who live with opioid use disorder in the emergency department (ED). A multi-disciplinary team developed a quality improvement project to implement this evidence. Methods: The intervention was developed by an expert working group consisting of specialists and stakeholders. The group set goals of increasing prescribing of buprenorphine/naloxone and providing next day walk-in referrals to opioid use disorder treatment clinics. From May to September 2018, three Alberta ED sites and three opioid use disorder treatment clinics worked together to trial the intervention. We used administrative data to track the number of ED visits where patients were given buprenorphine/naloxone. Monthly ED prescribing rates before and after the intervention were considered and compared with eight nonintervention sites. We considered whether patients continued to fill opioid agonist treatment prescriptions at 30, 60, and 90 days after their index ED visit to measure continuity in treatment. Results: The intervention sites increased their prescribing of buprenorphine/naloxone during the intervention period and prescribed more buprenorphine/naloxone than the controls. Thirty-five of 47 patients (74.4%) discharged from the ED with buprenorphine/naloxone continued to fill opioid agonist treatment prescriptions 30 days and 60 days after their index ED visit. Thirty-four patients (72.3%) filled prescriptions at 90 days. Conclusions: Emergency clinicians can effectively initiate patients on buprenorphine/naloxone when supports for this standardized evidence-based care are in place within their practice setting and timely follow-up in community is available.